Perlindungan Hukum terhadap Anak Jalanan sebagai Korban Tindak Pidana Kekerasan Fisik dalam Hukum Positif dan Hukum Pidana Islam - Desita Adinda Putri Lubis; Syaddan Dintara Lubis (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to examine the legal protections afforded to children on the streets who have been victims of haram actions from both an Islamic and a positive law viewpoint. Patient samples were collected from residents of Percut Sei Tuan District for this analysis. A variety of institutions and members of the community were interviewed and observed in order to gather data using qualitative methodologies. Law 35 of 2014 provides legal protection for victims of unlawful actions who are minors living on the streets, according to study results. Also included in this statute are measures that govern the proper penalty for offenders. Islamic law, on the other hand, provides a holistic view of the problem of child trafficking by highlighting the significance of human values and fairness in providing protection for these children. The investigation's results shed light on the many legislative safeguards put in place to keep homeless and victimised children safe. In light of this, it is clear that this endeavour is crucial with respect to positive law and Islamic law.